Charter and Revised Ordinances of the City of Hallowell, with Boundaries of the Wards 39 (1871) - (:unkn) unknown (My University, 1871)
§ 32: No person shall fire or discharge any gun or pistol from the top or window of any house or other building, or in any highway, public square, common or cemetery in the city.
Keywords: DISCHARGE